(untitled) (Kriminalističke teme, 2003)
In his work the author underlines that trafficking in human beings, as a specific form of criminal activity has been nowadays one of the top-tier issues engaging not only Judicial structures, criminologists and sociologists, but also the public and media, that is mass-communication means. This is a form of mostly organized, criminal activity with vast diversity of national and transnational content and characteristic. This phenomenon, by its nature, execution technique, goals aimed at, and multiple negative implications, especially on human rights protection field, represents a supra-national and supra-govemmental negative social occurrence as it touches conscience and feeling of humanity of every human and the whole mankind regardless io the racial, ethnic, sexual, national, geographic, religious, political or other affiliation or belief Therefore it is not surprising that significant international community’s activity that resulted in drawing-up a series of the conventions, declarations and recommendations as to prevent and suppress this negative social phenomenon, was dedicated to this problem. With regard to the fact that trafficking in human beings is evident on the territory of Bosnia and Herzegovina, as well as the obligation emerging from the conventions signed to incriminate all forms of behaviour that can be class fied as trafficking in human beings, the author highlights that the RS Criminal Code adopted in 2000 included incrimination of “trafficking in human beings for prostitution purposes”. This incrimination comprises only trafficking in human beings implying a sexual exploitation of a passive subject. However, the Criminal Code of BaH, which entered into force 31.03.2003 contains a couple of criminal acts comprising all kinds of behaviour implied in the international conventions by the notion of trafficking in human beings. In the end, the author stresses that trafficking in human beings is one of the most drastic forms of human rights and freedoms violation that requires vigorous actions on the side of the state on political and legislative field, as well as in the area of development of specialized bodies and structures for combating this form of criminal activity.